Psychosocial impact of COVID-19 pandemic: experience of healthcare workers in Qatar - Ahmad R. Al-Qudimat; Ahmad R. Al-Qudimat; Kalpana Singh; Emad Mustafa; Abdulqadir J. Nashwan; Raed M. Al-Zoubi; Raed M. Al-Zoubi; Raed M. Al-Zoubi; Aksam Yassin; Aksam Yassin; Omar M. Aboumarzouk; Omar M. Aboumarzouk; et al. (Frontiers Media S.A., 2023)
BackgroundThe COVID-19 pandemic has had a profound and global impact on healthcare systems worldwide, presenting unprecedented challenges for healthcare workers (HCWs) on the front. We aimed to evaluate the prevalence of anxiety and depression symptoms during the coronavirus pandemic among healthcare professionals in Qatar.MethodsA cross-sectional study where an electronic questionnaire containing demographics, and psychosocial questions were made on Google Docs and Microsoft Team, and were sent through email and WhatsApp to healthcare workers, including doctors, nurses, allied health and others working at Hamad Medical Corporation in Qatar, from June 1, 2021, to January 1st 2023. ANOVA, t-test and multiple linear regression were used to see the association between the psychological factors and sociodemographic variables using STATA version 17 software.ResultsA total of 829 participants were included in this study (response rate: 55%). The average age of the participants is 36.0 ± 7.1; 65.9% were males; 2.3% were doctors and 53% were nurses, 38.7% were allied healthcare professionals and 6% were others. Psychological, social effects, and workplace were shown to significantly related to their marital status, career, and hospital setting (p < 0.01 for each). Similar to this, dealing with COVID-19 patients and their education level with the length of time working at the designated facility were all connected with the health professional safety score (p < 0.05).ConclusionDuring the COVID-19 epidemic, healthcare workers in Qatar experienced a high incidence of negative psychosocial symptoms. To alleviate these outcomes, it would be useful to implement screening procedures for such symptoms and to devise preventive measures accordingly.